Physicochemical Characterization of Thermally Treated Chitosans and Chitosans Obtained by Alkaline Deacetylation - Ana Maria de Oliveira; Telma Teixeira Franco; Enio Nazaré de Oliveira Junior (International Journal of Polymer Science)
The thermal depolymerization of chitosan and alkaline deacetylation of chitin were characterized by measurement of viscosity, gel permeation chromatography (GPC), potentiometric titration (PT), and proton nuclear magnetic resonance spectroscopy (H1 NMR). The depolymerization rates (DR) measured by kinematic viscosity (KV), apparent viscosity (AV), and GPC (Mw) until 4 h of treatment were DRKV=21.9, DRAV=25.5, and DRMw=23.3% h-1 and for 5 to 10 h of treatment they decreased slowly to produce of DRKV=0.545, DRAV=0.248, and DRMw=1.11% h-1. The mole fraction of N-acetylglucosamine residues FA of chitosans was not modified after 10 h of thermal treatment at 100°C. The initial FA values of chitosan without any treatment were FAPT=0.21 and FAHNMR1=0.22 and of chitosan treated for 10 h were FAPT=0.27 and FAHNMR1=0.22. The variables used to characterize the depolymerization process showed a good correlation. Six hours of thermal treatment as sufficient to obtain chitosans with a molar mass 90% smaller than that of the control chitosan without treatment.